Advanced Technologies for Biomass - Di Carlo, Andrea; Savuto, Elisa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The use of biomass and organic waste material as a primary resource for the production of fuels, chemicals, and electric power is of growing significance in light of the environmental issues associated with the use of fossil fuels. For this reason, it is vital that new and more efficient technologies for the conversion of biomass are investigated and developed. Today, various advanced methods can be used for the conversion of biomass. These methods are broadly classified into thermochemical conversion, biochemical conversion, and electrochemical conversion. This book collects papers that consider various aspects of sustainability in the conversion of biomass into valuable products, covering all the technical stages from biomass production to residue management. In particular, it focuses on experimental and simulation studies aiming to investigate new processes and technologies on the industrial, pilot, and bench scales.